1974
DOI: 10.1007/bf00154975
|View full text |Cite
|
Sign up to set email alerts
|

Coronal heating by Alfv�n waves

Abstract: If Alfvrn waves are responsible for the heating of the solar corona, what are the various dissipation processes, under what conditions are they important, and what observational consequences may be expected? For wave periods longer than roughly one minute, the corona appears to the waves as turbulent and dissipation is efficient, but little more can be said. For shorter wave periods, a bend or twist in the magnetic field can convert Alfvrn waves into fast-mode waves, which then dissipate. But, if the waves tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(46 citation statements)
references
References 9 publications
1
43
0
Order By: Relevance
“…Alfvén waves produced by the constant turbulent convective motions in the subphotospheric region (Alfvén 1947) have been shown to transport enough energy to heat and maintain a corona ( Uchida & Kaburaki 1974;Wentzel 1974). This is known as the the Alfvén wave heating model (Hollweg et al 1982;Kudoh & Shibata 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Alfvén waves produced by the constant turbulent convective motions in the subphotospheric region (Alfvén 1947) have been shown to transport enough energy to heat and maintain a corona ( Uchida & Kaburaki 1974;Wentzel 1974). This is known as the the Alfvén wave heating model (Hollweg et al 1982;Kudoh & Shibata 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, extreme ultraviolet spectroscopic observations showed that the energy flux carried by acoustic waves in the upper chromosphere is too small to balance the observed energy losses of the corona (Athay & White 1979;Bruner 1981). Moreover, Skylab observations clearly showed that the corona consists of many magnetic loops (Vaiana et al 1973), suggesting a fundamental role of magnetic fields in the coronal heating process (Uchida & Kaburaki 1974;Wentzel 1974). Indeed, Golub et al (1980) found an empirical power-law relationship between thermal and magnetic properties of active regions:…”
mentioning
confidence: 99%
“…This theory was used by Chin & Wentzel (1972) and Wentzel (1974) to derive equations of the evolution of Alfvén waves, which we will employ. For the present reaction, neglecting spontaneous emission, Chin and Wentzel derived…”
Section: Low β-Plasmamentioning
confidence: 99%
“…Specifically, we employ the model of Chin & Wentzel (Chin & Wentzel 1972;Wentzel 1974) to calculate the evolution the Alfvén waves by assuming the sound waves generated in the interactions are quickly damped by the plasma. We present the result for two extreme cases of the plasma beta, namely…”
Section: Introductionmentioning
confidence: 99%